Parallel framework for earthquake induced response computation of the SDOF structure - Munir, Sarfraz; Hussain, Raja Rizwan; Islam, A. B. M. Saiful (Journal of Civil Engineering and Management, 2014)
Parallel computing briskly diminishes computation time through simultaneous use of multiple computing resources. In this research, parallel computing techniques have been developed to parallelize a program for obtaining a response of single degree of freedom (SDOF) structure under earthquake loading. The study uses Distributed Memory Processors (DMP) hardware architecture and Message Passing Interface (MPI) compilers directives to parallelize the program. The program is made parallel by domain decomposition. Concurrency in the program is created by dividing the program into two parts to run on different computers, calculating forced response and free response of the first half and the second half. Parallel framework successfully creates concurrency and finds structural responses in significant lesser time than sequential programs.